Inertia and couple-stress effects in a curvilinear thrust hydrostatic bearing - Walicka, Anna; Jurczak, Paweł; Falicki, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
The flow of a couple-stress lubricant in a clearance of a curvilinear thrust hydrostatic bearing with impermeable walls is considered. The flow in the bearing clearance is considered with inertia forces. The equations of motion are solved by an averaged inertia method. As a result , the formulae for pressure distributions without and with inertia effects were obtained. Radial thrust bearings and spherical bearings are discussed as numerical examples. It is shown that inertia effects influence the bearing performance considerably.
Keywords: couple-stress lubricant; inertia effects; hydrostatic thrust bearing